IMPLICATIONS OF COVID-19 PANDEMIC ON LAPAROSCOPIC AND ABDOMINAL SURGERY FOR BENIGN ADNEXAL CONDITIONS - SINGLE CENTER EXPERIENCE: Impact of COVID-19 pandemic on surgery - Dokic, Milan; Milosevic, Branislav; Dotlic, Jelena; Djeric, Teodora; Andric, Luka; Babic, Sandra; Sljivancanin, Dragisa (Medical Research, 2023)
Introduction/Aim: COVID-19 pandemic posed a challenge in patient treatment and caused problems in the organization of the health systems in many countries. The study aimed to analyze and quantify the influence of COVID-19 pandemic on performance of surgeries for benignant adnexal conditions with classic (open abdominal) and minimally invasive (laparoscopic) approach at the Clinic for Gynecology and Obstetrics University Clinical Center of Serbia. Material and Methods: The study retrospectively analyzed all patients who were operated due to benignant adnexal masses at our Clinic during the last five years. We compared numbers and types off operations before and during pandemic. Results: Study included 2166 patients who significantly more often had laparoscopic (61.9%) than open surgery (38.1%). Surgery of benignant adnexal masses was elective in 53.2% and emergency in 46.8%. Before the pandemic laparoscopic surgeries (mostly cystectomies) were on the rise. A reduction of laparoscopic and open surgeries was seen in the year 2020 (p=0.001). Moreover, majority of surgeries were emergency (76.2%; p=0.001). Nevertheless, this decrease was significant only for laparoscopic cystectomies (p=0.001), but not for adnexectomies (p=0.224) and salpingectomies (p=0.762). Likewise, the 2020 reduction of open cystectomies (p=0.073), adnexectomies (p=0.836) and salpingectomies (p=0.241) was also not significant. During the 2021, the number of surgical procedures for benignant adnexal masses again started to rise (p=0.023). No intra-hospital COVID-19 infections were registered. Conclusion: The total number of operations of benignant adnexal masses in our Clinic decreased and adjusted only to emergencies, which was mostly reflected in minimally invasive surgery.
Keywords: COVID-19, gynecological surgery, adnexal pathology, laparoscopy, laparotomy